TYPES OF CONSUMER BUYING BEHAVIOUR - Kumar, Mr. Ramesh; Singh Ahluwalia, Dr. Ishvinder; Dabas Hazarika, Dr. Deepti; Kumar, Kuldeep; Singh, Manjeet; Goswami, Prof. Chinmoy (The journal of contemporary issues in business and government, 2022)
Impact on consumer behaviour plays a very important role on the success of a product. All marketing efforts are directed towards influencing the consumer and for that marketer go for analysing different aspects of consumer behaviour and factors which influence their buying decisions. The purpose of study was to understand consumer, his buying behaviour and factors influencing his decision-making process. Introduction Consumer who is considered the king has always gathered the attention of a manufacturer. The needs of consumers are taken care of and products created which satisfy the consumer. Consumer behaviour is the reaction or response towards different products or companies. While taking a buying decision he goes through a proper survey to get all information regarding the product like the options available, benefits provided, company manufacturing it, benefits he gets and many more. The objective of the marketer is to present the product in a way that it can attract the consumer and convert him to a loyal customer. Marketer can anticipate the consumer reaction to their marketing strategies only if they are able to understand the motive of consumers which influence their behaviour (McKenzie, 1992). Consumer behaviour is formed by the personal experience, impact of social groups he has interaction with, services provided by the company, company background and companies goodwill. When a consumer goes for buying a product the impact of his peer group, experience, knowledge about the product and its alternatives, company history and most importantly the need satisfying capacity of the product play important role in decision making process.